Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Hasil Belajar PAI Siswa Di SMA Negeri 1 Kendari (IAIN KENDARI, 2023)
This study aims: 1) To determine the simultaneous effect of emotional intelligence and spiritual intelligence on student learning outcomes of PAI. 2) To determine the effect of emotional intelligence on student learning outcomes PAI. 3) To determine the effect of spiritual intelligence on student learning outcomes of PAI. This type of research uses a causality survey quantitative method. The research location was SMA Negeri 1 Kendari with a total population of 293 students and a sample of 72 students. Data collection techniques used were documentation and questionnaires, while data analysis techniques used descriptive analysis and inferential analysis. The results of research on students of SMA Negeri 1 Kendari show that: 1) Emotional intelligence and spiritual intelligence simultaneously have a direct and significant effect on student Islamic education learning outcomes, with a significance value of 0.037 <0.05, with a contribution of emotional intelligence and spiritual intelligence of 9.4 % of students' PAI learning outcomes. 2) Emotional intelligence has a positive and significant effect on student Islamic education learning outcomes, with a significant value of 0.023 <0.05, with the contribution of emotional intelligence to student learning outcomes of 7.4%. 3) Spiritual intelligence has a positive and significant effect on student Islamic education learning outcomes, with a significant value of 0.012 <0.05, with a contribution of spiritual intelligence to student learning outcomes of 8.9%.